MOTHER archetype in Ukrainian diary discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article emphasizes specific component of complex system of narrator in the context of diary dicourse – the archetype of Mother with following definition of its profound ethnocultural background and structural and semantic basis of both sociolingual and social and cultural phenomenon acquiring mithological status. It is stressed that a diary discourse narrator is able both to reflect reality universally and penetrate into its deep and eternal aspirations and desires. Correct appeal to collective unconscious is the key to obtain the intended effect. Archetyps are the most ancient universal forms of thinking represented in human minds as numerous collective images and symbols. They are coded and formalized samples as well as models of human behaviour. It is stated that all the images positioned in a diary discourse are weaved naturally into the text owing to mythological means of the interprettion of the world. While appealing to the mythologicl experience of the mankind and addressing to archetype phenomenon we interpret diary discourse as an important cultural component as it duplicates traditional ethological and artistic means which help both to interpret and reflect the reality. Role of Mother archetype in Ukrainian diary discouse has been specified. It has been determined that it is the most important, widespread and significant “eternal” image in the Ukrainian diary text medium. The connection between the archetype of Mother and archetype of Child, Destiny has been traced. Life priority of a woman-mother which means taking care of her famity has been specified. Influence of Mother archetype upon the formation of specific spiritual and emotional atmosphere of the Ukrainians has been determined; essential role of  woman-mother in the context of Ukrainian mental medium in terms of diary discourse has been characterized.
Keywords: diary discourse; archetype; archaic image; Mother archetype; narrator; ethnopsychology; mentality